ANALISIS IKLIM LINGKUNGAN BELAJAR DI SDN 3 CISANTANA - Imanudin; fisyabilla; Yusi Nurfatimah; Novi Kharisma; Tendi Maulana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to assess how safety, diversity, inclusivity, and health are integrated into the educational process at SDN 3 Cisantana to assess the learning environment. The issue arose as a result of the increasing need to ensure that schools facilitate social inclusion, psychological safety, and holistic development of students in addition to education. A descriptive qualitative approach was used in this study to collect data from educators, school administrators, and other staff members through interviews and observations. The results showed that the school has done a good job in creating an inclusive and respectful learning environment in the classroom, which is reinforced by constructive teacher-student relationships and differentiated instruction. The school has excellent infrastructure, a health unit, frequent sporting events, and disaster evacuation simulations. However, there is still room for improvement given the absence of formal written policies related to inclusive education, organized anti-bullying initiatives, and low student participation in health activities, such as student health agents. Although the school has made great strides in creating a positive learning environment, inclusive practices need to be formalized and preventive health education should be enhanced to ensure a safe, welcoming, and health-conscious learning environment.